Comparative study of data mining algorithm between orange and Weka: Theoretical study - Bouhrine, Fatiha; Tebaibia, Salima; Merabet, Bilel (The International tax journal, 2025)
This study aims to conduct a comparison between two important programs, namely Weka and Orange, in terms of several aspects, the most important of which are the algorithms used in both. The study reached several results, the most important of which is that both programs are open source.